Blood pressure standards for very low birthweight infants during the first day of life. Issue 3 (1st November 1999) - Lee, J; Rajadurai, V S; Tan, K W
Abstract : Blood pressures during the first day of life were measured prospectively in 61 very low birthweight infants using umbilical or peripheral arterial lines. Video recordings of real time waveforms were reviewed. Blood pressure correlated linearly with birthweight and gestation. Comparison with available standards showed that infants weighing under 800 g had lower acceptable mean arterial pressure (MAP). The lower limits of MAP for infants between 26 to 32 weeks of gestation were numerically similar to the gestational ages.